Stephen Ross, editor. Modernism, Theory, and Responsible Reading: A Critical Conversation. Bloomsbury Academic, 2022. - Anne Cunningham (Studies in 20th & 21st Century Literature, 2022)
Review of Stephen Ross, editor. Modernism, Theory, and Responsible Reading: A Critical Conversation. Bloomsbury Academic, 2022. 239 pp
Keywords: Modernism; affect theory; literary criticism; weak theory